Trafficked (My Story) - Hayes, Sophie (London Harper Collins Publishers, 2012)
When Sophie Hayes met the mysterious and charming stranger Bledi, she knew he would change her life - but she had no idea how much. At first, it was a typical whirlwind romance. But one day Bledi told Sophie that love always comes at a price. Bledi tricked Sophie into travelling to Italy, where he forced her into selling her body on the streets to help him pay off a large debt. When she refused, he beat her, stole her passport and locked the doors. Terrified and ashamed, Sophie worked the dangerous Italian streets without rest, seeing as many as 30 clients in a night. She was completely at Bledi's mercy for food, for clothes and for shelter. With no money, no friends and no family, she was trapped. But Sophie found the strength to keep going, clinging to life by a single thread of hope: that somehow she'd find a way to escape.
Keywords: Italy -- Great Britain -- Human trafficking victims